Bioinformatics-based strategies to identify PFHBII-causing and HCM main locus and/or HCM modifying mutations - Yako, Yandiswa (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2004.